A Step Toward Timely Referral and Early Diagnosis of Cancer: Implementation and Impact on Knowledge of a Primary Care-Based Training Program in Botswana - Tapela, Neo M.; Peluso, Michael J.; Kohler, Racquel E.; Setlhako, Irene I.; Botebele, Kerapetse; Gabegwe, Kemiso; Nkele, Isaac; Narasimhamurthy, Mohan; Mmalane, Mompati; Grover, Surbhi; Barak, Tomer; Shulman, Lawrence N.; et al. (Frontiers in Oncology, 2018)
Introduction: Health system delays in diagnosis of cancer contribute to the glaring disparities in cancer mortality between high-income countries and low- and middle-income countries. In Botswana, approximately 70% of cancers are diagnosed at late stage and median time from first health facility visit for cancer-related symptoms to specialty cancer care was 160 days (IQR 59-653). We describe the implementation and early outcomes of a training targeting primary care providers, which is a part of a multi-component implementation study in Kweneng-East district aiming to enhance timely diagnosis of cancers. Methods: Health care providers from all public facilities within the district were invited to participate in an 8-hour intensive short-course program developed by a multidisciplinary team and adapted to the Botswana health system context. Participants' performance was assessed using a 25-multiple choice question tool, with pre- and post-assessments paired by anonymous identifier. Statistical analysis with Wilcoxon signed-rank test to compare performance at the two time points across 8 sub-domains (pathophysiology, epidemiology, social context, symptoms, evaluation, treatment, documentation, follow-up). Linear regression and negative binomial modeling were used to determine change in performance. Participants' satisfaction with the program was measured on a separate survey using a 5-point Likert scale. Results: 176 participants attended the training over five days in April 2016. Pooled linear regression controlling for test version showed an overall performance increase of 16.8% after participation (95%CI 15.2-18.4). Statistically significant improvement was observed for seven out of eight subdomains on test A and all eight subdomains on test B. Overall, 71 (40.3%) trainees achieved a score greater than 70% on the pre-test, and 161 (91.5%) did so on the post-test. Participants reported a high degree of satisfaction with the training program's content and its relevance to their daily work. Conclusions: We describe a successfully implemented primary health care provider-focused training component of an innovative intervention aiming to reduce health systems delays in cancer diagnosis in sub-Saharan Africa. The training achieved district-wide participation, and improvement in the knowledge of primary health care providers in this setting.